Forest Destruction on Sumbawa Island West Nusa Tenggara in An Ecological Justice Perspective - M. Yahya; Taufik Firmanto; G Gufran; S Sukirman; A Adnan; Muhamad Amin (Universitas Muhammadiyah Surakarta, 2023)
This article is the result of legal research that analyzes forest management policies by the regional government of West Nusa Tenggara (NTB), especially on the island of Sumbawa, in relation to increased production of corn planting which has resulted in an environmental crisis in the form of forest destruction. The purpose of this study was to analyze forest destruction on Sumbawa Island, West Nusa Tenggara Province from the perspective of Ecological Justice, by conducting an analysis of forest management policies on Sumbawa Island. The method used in this study is a normative research method with a conceptual approach, statutory approach, and analytical approach. The results of this study indicate that there has been massive forest destruction, many of the forests on the island of Sumbawa have been denuded by the expansion of community farming land. This is the cause the occurrence of floods in the rainy season and drought in the dry season which often occur every year, especially in the districts of Sumbawa, Dompu, Bima Regency and Bima City. Government policies that are more progressive and environmentally friendly are needed in cope damage forests, with a priority on economic growth as well as taking into account the conditions of the community and environmental conditions with an outlook on ecological justice.